MOLECULAR DOCKING INSIGHTS INTO PROBIOTICS SAKACIN P AND SAKACIN A AS POTENTIAL INHIBITORS OF THE COX-2 PATHWAY FOR COLON CANCER THERAPY - BAQI, MOHD ABDUL; JAYANTHI, KOPPULA; RAJESHKUMAR, RAMAN (International Journal of Applied Pharmaceutics, 2025)
Objective: This study aims to explore the interactions between probiotics-derived bacteriocins and the COX (cyclooxygenase) pathway, particularly focusing on the cancer-associated COX-2 (cyclooxygenase-2) enzyme (PDB ID: 6COX). The goal is to assess the potential of these bacteriocins as inhibitors of COX-2, investigating their possible anti-cancer effects through modulation of this key enzyme involved in cell growth and survival pathways. Methods: Using the Glide module, the study first involved the molecular docking of bacteriocins. Next, an Absorption, Distribution, Metabolism, and Excretion (ADME) study was conducted using Qikprop. The Prime Molecular Mechanics Generalised Born Surface Area (MM-GBSA) method was used to calculate binding free energy. Results: Four bacteriocins demonstrated significant binding affinity and interactions, including hydrogen and hydrophobic bonds, with key residues such as Tyr385, Ser530, Tyr355, Arg120, Phe518, and Leu352, in the associated COX-2 enzyme(PDB ID: 6COX). Among these, Sakacin P exhibited an excellent XP-docking score of-6.73 kcal/mol, indicating strong binding potential. Prime MM-GBSA analysis revealed promising binding affinities with ΔBind (-90.85 kcal/mol), ΔLipo (-64.81 kcal/mol), and ΔVdW (-46.34 kcal/mol). The ligand consistently interacted with residues Tyr355, and Arg120. Conclusion: Sakacin P bacteriocin, characterized by functional groups including the primary amine (NH₂), and oxygen (O), demonstrates significant potential as a COX-2 enzyme inhibitor. This suggests its promising application as an anti-cancer agent, particularly for colon cancer.